SISTEM INFORMASI PENJUALAN DENGAN MENERAPKAN METODE SALES FORCE AUTOMATION - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
The sales process is the most important part of the product manufacturer or the company being ditributor. Conventional sales system by the way telephone or consumer come directly to know the available or not the product needed to make consumers should take the time to do that. Such conditions can also lead to consumer dissatisfaction especially if the desired item is unavailable. Dissatisfaction with customer service can affect the indication of declining sales turnover. For that, the company needs a website-based sales information system that can be accessed by consumers anytime and anywhere so that it can expand its marketing area, and can facilitate salespeople to conduct promotions to Community. This research produces the sales information system by implementing a sales Force Automation (SFA) method which is expected to maximize the sales and focus of services to customers.